Kajian Intertekstual pada Novel Jepun Negerinya Hiroko dengan Kuantar Ke Gerbang - Runtuwarouw, Jourike; Komarudin, Mochamad Arief (Vocational College of Diponegoro University, 2026)
This study aims to describe the intertextual relationship between the novels Jepun Negerinya Hiroko and Kuantar ke Gerbang, including comparisons of the main male characters, themes, plots, meanings, and points of view in both novels. The research employs a descriptive qualitative method with an intertextual approach. Data were collected through library techniques and validated using theoretical and data triangulation. Analysis results reveal that both novels share similarities and differences in their structural elements. The similarities include the selfish attitude of the main male characters, themes addressing social problems encompassing human life in macro and micro aspects that influence marital relationships, point of view using first-person singular style where in Jepun Negerinya Hiroko the narrator participates as a character in the story, while in Kuantar ke Gerbang the narrator exists outside the story but understands the characters' feelings, and an overall meaning of unity among people. In Jepun Negerinya Hiroko, universalism is emphasized to unite different ethnic groups through the slogan promoting freedom, brotherhood, and equality, whereas Kuantar ke Gerbang highlights nationalism through youth unity. The differences between the two novels include the main male character being introverted in Jepun Negerinya Hiroko and extroverted in Kuantar ke Gerbang, the role of the main male character as antagonist versus protagonist, the central theme concerning mixed marriage between different cultural and national backgrounds compared to the spirit of national independence struggle, and the use of flashback plot positioned at the end of the story in Jepun Negerinya Hiroko.